Pelaksanaan Diversi terhadap Anak dalam Melakukan Tindak Pidana Laka Lantas di Wilayah Hukum Poles Bangli - I Kadek Dwi Giri Astawan; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2025)
Traffic problems faced by the Indonesian state are increasing. The problems that are often encountered are worse because of the rampant traffic accidents caused by minors. In this study the author will discuss the implementation of Diversion of children in committing criminal acts of traffic accidents in the Bangli Police District and what factors are an obstacle in the implementation of Diversion of children in committing criminal acts of traffic accidents in the Bangli Police District. The writing of this thesis uses empirical methods as well as statutory, conceptual, and case approaches. The results of this study indicate that the implementation of Diversion against children in the crime of traffic offenses in the jurisdiction of Bangli Police Station during the settlement of cases directed by Diversion has been carried out properly and obstacles in the implementation of Diversion against minors in the crime of traffic offenses in Bangli Police Station, including internal and external factors.